Ya’juj dan Ma’juj Dalam QS. Al-Kahfi Telaah Pemikiran Imran Nazar Hosein - Sinaga, Almi Try Azwar (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
Millions of human beings in today's modern era, continue to research the truth of the contents in the Qur'an. As is well known, the Qur'an contains nature, laws, orders, prohibitions, and contains stories in the past and in the future. One of them is surah al-Kahf which is about Gog and Magog. This article uses library research with a descriptive-analytic approach. Imran Nazar Hosein interpreted Gog and Magog in surah al-Kahf using the maudhu'i method. He examined Gog and Magog as mufsidun fil ard whose arrival would change the world order to become godless. And the return of the Jews to Jerusalem with the help of Gog and Magog.